Analysis of Emotional Intelligence, Compensation and Career Path on Tour Guide Performance Through Job Satisfaction - Muhammad Yusuf; Uus Mohammad Darul Fadli; Esti Liana; Jarot Santosa; Murni S ulistyowati (Greenation Research & Yayasan Global Resarch National, 2024)
The purpose of this literature study is expected to build a hypothesis regarding the influence between variables that can later be used for further research in the scope of human resource management. The literature review research article on the analysis of emotional intelligence, compensation and Career Path on tour guide performance through job satisfaction is a scientific literature article in the scope of human resource management science. The approach used in this literature review research is descriptive qualitative. The data collection technique is to use literature studies or conduct a review of relevant previous articles. The data used in this descriptive qualitative approach comes from previous research that is relevant to this research and is sourced from academic online media such as the Thomson Reuters Journal, Springer, Taylor & Francis, Scopus Emerald, Elsevier, Sage, Web of Science, Sinta Journal, DOAJ, EBSCO, Google Scholar and digital reference books. In previous studies, 1 relevant previous article was used to review each independent variable. The results of this literature review article are: 1) Emotional Intelligence influences Job Satisfaction; 2) Compensation influences Job Satisfaction; 3) Career Path influences Job Satisfaction; 4) Emotional Intelligence influences Tour Guide Performance; 5) Compensation influences Tour Guide Performance; 6) Career Path influences Tour Guide Performance; 7) Job Satisfaction influences Career Path; 8) Emotional Intelligence influences Tour Guide Performance through Job Satisfaction; 9) Compensation influences Tour Guide Performance through Job Satisfaction; and 10) Career Path influences Tour Guide Performance through Job Satisfaction.